Testing the feasibility of blood flow restriction training to enhance the HEALTH benefits of exercise in individuals with type 2 diabetes (BOOST-HEALTH Trial): Study Protocol - Amy M Thomson; Seth F McCarthy; Jamie F Burr; Jonathan P Little; Maryam Kebbe; Martin Sénéchal (PLoS ONE, 2026)
Introduction Individuals with type 2 diabetes (T2D) display reduced cardiorespiratory fitness, a strong predictor of premature mortality and T2D-related complications. Aerobic training (AT) enhances cardiorespiratory fitness and is a cornerstone in T2D management. Emerging data suggest that AT combined with blood flow restriction (AT+BFR) may elicit greater improvements in cardiorespiratory fitness than typical AT in healthy individuals. However, the feasibility and effects of AT+BFR in individuals with T2D remain unclear. Objectives This protocol describes the BOOST-HEALTH trial, which aims to 1) evaluate the feasibility of a 6-week AT+BFR intervention in adults with T2D, and 2) estimate preliminary effect sizes for changes in cardiorespiratory fitness, glycemic outcomes, and quality of life compared with standard care AT (AT- stdCare). Methods BOOST-HEALTH (NCT07196371) is a single-blinded, multisite, randomized clinical pilot trial with two parallel treatment arms. Sixty adults with T2D (n = 30 female) will be randomized to 6 weeks of AT+BFR or AT-stdCare. Both groups will complete supervised treadmill walking three times per week (96 min/week) at 40–50% heart rate reserve. The AT+BFR group will exercise with BFR cuffs inflated to 60–80% of limb arterial occlusion pressure, whereas the AT-stdCare group will exercise without BFR. Primary outcomes will assess feasibility, including recruitment, enrollment, adherence, and retention. Secondary outcomes will estimate effect sizes for changes in cardiorespiratory fitness (VO 2max ) and continuous glucose monitoring metrics to inform outcome selection and sample size calculations for future definitive trials. Outcomes will be assessed at baseline and post-intervention. Discussion Results of this study could establish BFR training as a novel therapeutic modality to augment the effects of exercise in individuals with T2D. Findings will inform whether a larger, definitive efficacy trial is warranted and will guide exercise professionals on the potential integration of AT+BFR as an alternative strategy to enhance the benefits of exercise in this population.